Immunomodulatory and Histoprotective Effects of Luteolin and Related Flavonoids in Autoimmune Thyroiditis: Evidence from A Rat Model - Kayumov, Khasan; Kuchkarova, Lubov; Durá-Travé, Teodoro; Petrenko, Sergei; Ergashev, Nurali; Abdurakhmonov, Jakhongir; Achilov, Rashidbek; Khan, Shoaib; Pulatova, Visola; Ernazarov, Mirsaid (Trends in Sciences, 2025)
Autoimmune thyroiditis (AIT), particularly Hashimoto’s thyroiditis, is a common endocrine disorder characterized by immune-mediated follicular destruction, lymphocytic infiltration, and hormonal imbalance. Current management relies mainly on hormone replacement therapy, which does not address underlying immune dysregulation. This study evaluated the immunomodulatory, antioxidant, and histoprotective effects of 3 plant-derived flavonoids - quercetin, dihydroquercetin, and luteolin - in an experimental rat model of AIT. Thirty male Wistar rats were divided into 5 groups: Healthy control, untreated AIT, and AIT treated with quercetin (25 mg/kg/day), dihydroquercetin (20 mg/kg/day), or luteolin (10 mg/kg/day) for 14 days. AIT was induced by bovine thyroglobulin with Freund’s adjuvant. Serum anti-thyroid peroxidase (anti-TPO) antibodies, thyroid-stimulating hormone (TSH), metabolic parameters, and liver/pancreatic enzyme activity were measured. Histological analysis assessed thyroid architecture and lymphocytic infiltration. All flavonoids significantly reduced anti-TPO titers and normalized TSH, glucose, lipid, and uric acid levels. Luteolin showed the strongest effect, decreasing anti-TPO by 63%, restoring liver enzyme activity, improving lipid/glucose metabolism, and reducing lymphocytic infiltration. Histologically, luteolin preserved thyroid follicular integrity and prevented tertiary lymphoid structure formation. Luteolin demonstrated superior immunomodulatory and metabolic benefits compared to quercetin and dihydroquercetin, highlighting its translational potential as an adjunctive therapy for autoimmune thyroiditis. HIGHLIGHTS Luteolin, quercetin, and dihydroquercetin exerted strong immunomodulatory, antioxidant, and histoprotective effects in an experimental autoimmune thyroiditis (AIT) rat model. Luteolin showed the greatest efficacy, reducing anti-TPO antibodies by 63%, normalizing TSH, and improving metabolic parameters. Flavonoid treatment corrected AIT-induced hyperglycemia, dyslipidemia, and hyperuricemia, restoring systemic biochemical balance. Histological and biochemical evaluations confirmed luteolin’s ability to preserve thyroid architecture, restore endocrine balance, and prevent tertiary lymphoid structure formation. GRAPHICAL ABSTRACT